Community structure of bivalve in the Curah Ombo River Estuary, Java, Indonesia - Kustiawan Tri Pursetyo; Endang Dewi Masithah; Mohd Hanafi Idris; Luthfiana Aprilianita Sari (Depik, 2025)
Curah Ombo River is an estuarine water body with a muddy substrate that serves as the optimal habitat for bivalves. However, this water body experiences fluctuations in water conditions originating from both terrestrial sources and climate change. The impacts of these conditions trigger changes in the biological conditions, including bivalves.The objective of this study was to determine the diversity index, uniformity index, dominance index, and species richness index of bivalve molluscs found in the Curah Ombo River from Marchto June. The research parameters included identification, diversity index values (H'), uniformity (E), dominance (C), and species richness (R). Water quality was also measured as a supporting factor, including depth, temperature, dissolved oxygen (DO), pH, salinity, and brightness. All data were analyzed for their relationships using Principal Component Analysis (PCA). The results obtained at three points revealed nine species: Paratapes sp., Anadara antiquata, Anadara transversa, Anadara granosa, Meretrix meretrix, Scapharca pilula, Mytilus placuna, and Atrina pectinata. Point 2 showed the highest values for most diversity index values (H'), uniformity (E), dominance (C), and species richness (R), exceeding points 1 and 3. The results of Principal Component Analysis (PCA) show that total bivalve mollusks are categorized into one category together with salinity, light intensity, location, dissolved oxygen (DO), depth, and temperature.Keywords:MarineAquacultureInvertebratesLife feedEnvironmentEconomy